Reproductive Markers of Testicular Function and Size During Puberty in Boys With and Without a History of Cryptorchidism - Rodprasert Wiwat; Koskenniemi Jaakko J; Virtanen Helena E; Sadov Sergey; Perheentupa Antti; Ollila Helena; Albrethsen Jakob; Andersson Anna-Maria; Juul Anders; Skakkebaek Niels E; Main Katharina M; Toppari Jorma (Endocrine Society, 2022)
Context
Longitudinal data on levels of hypothalamic-pituitary-gonadal axis hormones and insulin-like growth factor I (IGF-I) during puberty in boys with a history of cryptorchidism are largely missing.
Objective
We aimed to compare pubertal hormone levels between boys with a history of congenital cryptorchidism who experienced spontaneous testicular descent or underwent orchiopexy and boys without a history of cryptorchidism.
Methods
This was a nested case-control study within a population-based birth cohort, with a prospective, longitudinal pubertal follow-up every 6 months (2005 to 2019). Participants were 109 Finnish boys, including boys with a history of unilateral cryptorchidism who underwent orchiopexy (n = 15), unilateral cryptorchidism who had spontaneous testicular descent (n = 15), bilateral cryptorchidism who underwent orchiopexy (n = 9), bilateral cryptorchidism who had spontaneous testicular descent (n = 7), and controls (n = 63). Serum reproductive hormone levels and testicular volumes were measured.
Results
From around onset of puberty, boys with bilateral cryptorchidism who underwent orchiopexy had significantly higher follicle-stimulating hormone (FSH) and lower inhibin B levels than controls. Boys with unilateral cryptorchidism who underwent orchiopexy had significantly higher FSH than controls, whereas inhibin B levels were similar. Testosterone, luteinizing hormone, insulin-like factor 3, and IGF-I were generally similar between groups. Testicular volume of boys with unilateral or bilateral cryptorchidism who underwent orchiopexy was smaller than that of the controls from 1 year after pubertal onset (P < 0.05).
Conclusion
Cryptorchid boys, particularly those with bilateral cryptorchidism who underwent orchiopexy, had altered levels of serum biomarkers of Sertoli cells and germ cells and smaller testicular volumes compared with controls.